Determination of Palladium in Surface Water and Gold Ore Samples by Flame Atomic Absorption Spectrophotometry After Pre-concentration with the Porous Nano-calcium Titanate by Sorghum Straw Template Method - Li, Yan; Zhang, Dong (Asian Journal of Chemistry, 2014)
A new solid-phase extraction method is described for the determination of traces of palladium in water and geological samples by flame atomic absorption spectrophotometry. The method is based on sorption of Pd ion on the porous nano-calcium titanate by sorghum straw template method (SPCTO). The possible parameters influencing the enrichment were optimized. In the pH range of 4-7, the Pd ion could be quantitatively retained by the SPCTO. The Pd ion adsorbed on the SPCTO could be completely eluated by using 0.1 mol/L HNO3. The enrichment factor was more than 200. Under the optimal solid-phase extraction conditions, the method detection limit was 0.017 ug/L. The established method has been successfully applied to analyze surface water and geological samples. Its accuracy was evaluated by standard addition method and the R.S.D. (n = 6) within 4.07 %. The recoveries were in the range of 93.8 to 100.9 %.